Aborcja w orzecznictwie Sądu Najwyższego USA - Demenko, Anna (Czasopismo Prawa Karnego i Nauk Penalnych, 2020)
The paper presents the analysis of the jurisprudence of the US Supreme Court in cases concerning criminalization and admissibility of abortion which fundamentally influences the law in force concerning abortion in the US. In particular, attention is given to arguments stated by individual judges and justification of their judgments. The paper confronts conclusions from reading the justifications of the decisions of the US Supreme Court and the accompanying opinions of scholars with the only Polish decision in this respect that has been published so far, i.e. the judgment of the Constitutional Tribunal of May 28, 1997, as well as with numerous judgments of the European Court of Human Rights (ECHR). In the conclusion, it is argued that there are certain important similarities between the Strasbourg and the American approach to the rationale behind a legal intervention in the procedure of terminating a pregnancy, while significant differences in the approach to available methods and purpose of imposing restrictions on abortion remains.